Forum 1: Migrant climate in the Kinocene. Issue 3 (4th May 2019) - Nail, Thomas
ABSTRACT: In this intervention, I put forward five short theses on the topic of 'Anthropocene mobilities.' My aim is not to unpack every concept contained herein but rather to provide a provocative introductory synthesis of five big ideas about Anthropocene mobility for further discussion. 1) We are living in the Kinocene, 2) The ontology of our time is an ontology of motion, 3) We need a new movement-oriented political theory to grapple better with the mobile events of our time. We need a kinopolitics, 4) Climate change is a weapon of primitive accumulation. 5) The Kinocene presents us with the danger of new forms of domination (a new colonialism, a new climate capitalism, new states, and new borders) but also with the opportunity for a new revolutionary sequence.